Implementation of the SAW Method in the Decision Support System for Giving Rewards for Honorary Employees - Fikri Akbar Sitompul; Fauriatun Helmiah; Rohminatin Rohminatin (Building of Informatics, Technology and Science (BITS), 2022)
Giving rewards to employees is one way to increase morale and improve performance for employees who excel. At the District Financial and Asset Management Agency. Asahan in choosing the best employees, the workload cannot be used as the only reference for the awarding of these rewards. However, there are several criteria that are also considered in giving rewards. So we need a decision support system to help the selection of the best employees. Temporary employees who are in government agencies have a percentage of 10% of the total number of registered employees. Every year, honorary employees renew their contract letters to continue their work. This is the basis for giving rewards or bonuses so that honorary employees are motivated to work and give the best results in carrying out and assisting civil servants in the government environment. The process of giving this reward was previously carried out manually, which is based on only one criterion, namely only from attendance. This makes it difficult to make decisions about the best honorary employees who are entitled to receive rewards. This consideration process is considered ineffective due to the different workloads of each honorary employee. To overcome the existing problems, we need a system in the form of a decision support system. It is hoped that this research will be able to determine the three best employees who are entitled to rewards in accordance with the performance criteria by calculating each weight of the criteria that have been set.